Multidisciplinary Public Health : Understanding the Development of the Modern Workforce - Wright, Jenny (Book collections on Project MUSE., 2014)
A lively and comprehensive review of policy change in England, making useful comparisons with the rest of the UK. It includes the voices of key protagonists in the development of the public health workforce.